2014
DOI: 10.6026/97320630010716
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity evaluation of low doses of pesticides in individual and mixed condition on human keratinocyte cell line

Abstract: The induced toxicity of three pesticides (alpha-Hexachlorocyclohexane: α-HCH; Parathion methyl:PM; Carbofuran: CN) in single and four possible combination on human keratinocyte cell line have been investigated. There was no significant change in toxicity (cyto and genotoxicity) on cell line exposed by individual pesticides except α-HCH. But, a synergistic effect was observed when we tested mixture of pesticides. The intracellular ROS and cytotoxicity assay revealed maximum reduction in cell viability (60%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Results showed that both agents enhanced ROS production. This is in accordance with the nding that α-HCH increased the ROS generation in keratinocytes [42] and that propanil induced lipid oxidation in rat models [43]. Mitochondria are the main source of intracellular ROS, and the ΔΨ was closely related to ROS production [44,45].…”
Section: Discussionsupporting
confidence: 89%
“…Results showed that both agents enhanced ROS production. This is in accordance with the nding that α-HCH increased the ROS generation in keratinocytes [42] and that propanil induced lipid oxidation in rat models [43]. Mitochondria are the main source of intracellular ROS, and the ΔΨ was closely related to ROS production [44,45].…”
Section: Discussionsupporting
confidence: 89%
“…For examples, Caron-Beaudoin et al 6 reported the adverse effects of atrazine on human adrenocortical carcinoma (H295R) and primary umbilical vein endothelial (HUVEC) cells 6 . Abhishek et al 7 reported the toxicity of three pesticides (i.e., alpha-hexachlorocyclohexane, parathion methyl and carbofuran) on human keratinocyte cells 7 .…”
mentioning
confidence: 99%
“…In another study, HaCat cells were used to assess the combined effect of low dose of a mixture of three pesticides (lpha-hexachlorocyclohexane, parathion methyl and carbofuran). Results revealed that mixed pesticides were more hazardous for human health, exerting a high toxicity with respect to individual ones [75]. Deleterious consequences have been observed also with other organophosphate pesticides (such as omethoate and methamidophos) inducing different levels of cyto and genotoxic effects in human cell lines [76].…”
Section: Toxicological Studymentioning
confidence: 98%